Enhancing Thai elementary students' English and maintaining Thainess using localized materials: Two putative confronting forces - Budsaba Kanoksilapatham; Todsapon Suranakkharin (Universitas Syiah Kuala, 2021)
In Thailand, concerns over the imperative need to improve its citizens' English proficiency and the unsatisfactory English learning outcomes have long been present. In addition, ongoing globalization has raised another concern that Thainess is being eroded due to external influences. This study attempted to compromise these two seemingly conflicting forces by enhancing Thai students' global English and maintaining local Thainess associated with three regions of Thailand. First, a set of instructional innovations for elementary English education was constructed in each region. These were based on prominent characteristics of local Thainess elicited through a questionnaire completed by local community members and subsequently implemented in Grade 4 classes at three schools in each region of Thailand for ten weeks. Next, two separate sets of pretests-posttests corresponding to each instructional set were constructed and administered to assess their local Thainess and English knowledge. Finally, to ensure that the knowledge gained from the instruction was put into practical use, a tour guide simulation task was conducted by the students. The analysis of the test scores demonstrates that localized lessons were beneficial, enhancing their local Thainess knowledge and associated English vocabulary. The accomplishment of the task thus represented their knowledge of local Thainess and English, contributing to a sense of pride in their nation and a sense of achievement in their English proficiency and instruction.